DINAMIKA PENGANGGURAN DI DAERAH ISTIMEWA YOGYAKARTA - Tukiran Tukiran; Endang Ediastuti Mustar (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2005)
Lowest number of population increasing is not being supported with the increasing of labor market. This has caused many forms of unemployment problem. The unappropriated quality between supply and demand of employment has trigged multidimensional problems in the job market. Empowerment of agricultural sector, informal sector and friendly manpower kind of industry along with the local entrepreneur reinforcing will be the important aspect in handling this kind of matter. Aside from that, the limitation of local capability should be upgraded with placing the employees to another countries or areas, such as AKAD and AKAN.